2003
DOI: 10.1037/0021-9010.88.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multisource feedback and a feedback facilitator on the influence behavior of managers toward subordinates.

Abstract: The authors compared a feedback workshop with both a no-feedback control group and a comparison group of managers who received a feedback report but no feedback workshop. The multisource feedback was based on ratings of a manager's influence behavior by subordinates, peers, and bosses. Managers in the feedback workshop increased their use of some core influence tactics with subordinates, whereas there was no change in behavior for the control group or for the comparison group. The feedback was perceived to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 31 publications
4
110
0
Order By: Relevance
“…This finding is congruent with other studies (Seifert et al 2003;Sargeant et al 2008;Stalmeijer et al 2010). The three sources did not seem to have the same impact, though.…”
Section: Feedback Use In Pdpssupporting
confidence: 82%
“…This finding is congruent with other studies (Seifert et al 2003;Sargeant et al 2008;Stalmeijer et al 2010). The three sources did not seem to have the same impact, though.…”
Section: Feedback Use In Pdpssupporting
confidence: 82%
“…This creates a challenge in the context of Accreditation Council for Graduate Medical Education (ACGME) requirements for use of multisource feedback in resident evaluations. 23,25 We also found that a concerning number of our responders reported not giving any feedback at all to the residents, highlighting the challenges of creating an educational environment where staff feedback is expected and encouraged. It also underscores the importance of asking staff members the appropriate questions to allow them to feel more comfortable with and engaged in the resident evaluation process.…”
Section: Discussionmentioning
confidence: 92%
“…7,15,22 Think-aloud interviews by Mazor et al 19 revealed that raters frequently base their evaluations on general impressions rather than directly observed behaviors, and they had different interpretations of the desired behaviors they were rating. 15,23 Although training has been shown to improve faculty ability to give feedback, nonphysician staff members who participate in multisource feedback rarely receive comparable training. 24 Our findings add to the knowledge about competencies that nonphysician staff members feel competent and comfortable in evaluating.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have pointed out that merely reading an analysis of ratings by students or being aware of weaknesses does not automatically incite teachers to reflect on and look for ways to improve their teaching practice (Atwater et al 2002;Seifert et al 2003;Smither et al 2005). Moreover, there is evidence that unfacilitated feedback can cause negative emotional reactions, like denial and defensiveness, which can even raise barriers to reflection (DeNisi & Kluger 2000;Sargeant et al 2008;Overeem et al 2009) and behavioural change (Sargeant et al 2008).…”
Section: Introductionmentioning
confidence: 99%